Common Illness Behaviour, and Preferred Treatment Options among Inhabitants of a Rural Community in Enugu State, Nigeria - Ndibuagu, Edmund O.; Ifeanyi, Godwin C.; Odo, Amechi J. (British Journal of Healthcare and Medical Research, 2026)
Factors that influence behaviour when ill, include; culture, beliefs, knowledge, values, finances, time, materials, educational level, and influence of other people. Illness behaviour is the ways in which given symptoms may be differently perceived, evaluated, and acted (or not acted) upon by persons. This descriptive, cross-sectional study was conducted at Opi town, Nsukka Local Government Area, Enugu State, Nigeria. Inhabitants of the town, that presented for medical outreach programme in 2019 participated. Most of the respondents (94.2%) were aged 20 to 79 years, with majority being females (76.5%). All belonged to Igbo tribe, and Christians; while 70% were married. Majority had primary level education (38.7%). Overall, 68.3% would seek medical care as first reaction to illness. Most respondents sought medical care at the Patent and Proprietary Medicine Vendour (PPMV) shop (47.3%). Up to 45.7% always paid their medical bill without difficulty, while 11.5% were never able to pay their medical bill without difficulty. Also, 29.2% always sought for help before paying medical bills, but 24.7% never sought for help before paying for medical bills. In comparing orthodox medical care with traditional treatment, 65.4% perceived orthodox medical care as always being superior to traditional treatment, while only 2.1% did not perceive orthodox medical care as being superior. Majority of the inhabitants of Opi town will usually seek medical care when ill, and PPMV shop is most frequently patronized. Most people in Opi town also have the perception that orthodox medical care is superior to traditional treatment.